PENGARUH VIRAL MARKETING TERHADAP NIAT BELI KONSUMEN - Saripudin, Asep; Rahayu, Agus; Wibowo, Lili Adi (Jurnal Ilmu Manajemen dan Bisnis, 2022)
Digitalization has penetrated almost all sides of life, people are trapped by internet technology. It has created very tight competition within business ventures where are companies are struggling to introduce and sell their products to the market faster than before. The speed of conveying information and the attractiveness of the products offered is one of the ways company steal customers's attention  Viral Marketing is helped company to delivered information faster like a virus. Viral marketing can penetrate the message of a product to all demographic, geographical and other segments so that it becomes a marketing force The dimensions that support viral marketing in this study are the ease of access to information, transaction security, and conformity to information.The study was conducted through questionnaires as many as 21 questions to 100 respondents. The result of the correlation / R relationship is 0.620, then from the output the terminated coefficient is 0.385 which means that the influence of the independent variable (viral marketing) on the dependent variable (purchase intention) is 38.5%. The T test shows that the value of t count is 6,582 T table 1,984, this shows that the variable X viral marketing has an influence on the variable intention to buy Y.